Pemidanaan terhadap Pelaku Tindak Pidana Penebangan Hutan Tanpa Izin Berdasarkan Trilogi Tujuan Hukum - Septiani, Annisa Eka; Shafira, Maya; Tamza, Fristia Berdian; Firganefi, Firganefi (Penerbit Goodwood, 2024)
Purpose: This study aims to analyze the punishment of perpetrators of unlicensed logging based on the trilogy of legal objectives: justice, legal certainty, and expediency. Methodology: The research method used is juridical-normative with a qualitative descriptive approach. This research focuses on analyzing Decision No. 379/Pid.B/LH/2023/PN.Tjk, supported by literature studies and secondary data in the form of laws and regulations. Results: The results showed that the criminalization in the cases studied tended to prioritize aspects of legal certainty, such as the enforcement of formal legal norms. However, aspects of substantive justice, especially for affected communities, have not been fully achieved. Likewise, legal expediency related to efforts to prevent environmental damage still requires strengthening to have a broader impact. Conclusion: This study highlights that the punishment of perpetrators involved in illegal deforestation must align with the three primary goals of law: legal certainty, justice, and utility. Legal certainty requires clear and consistent sanctions to deter illegal activities. Justice demands proportional punishment based on the environmental damage caused, while utility emphasizes the long-term benefits of punishment, such as ecosystem restoration and community welfare. Therefore, applying the trilogical goals of law in sentencing offenders for illegal deforestation can strike a balance between environmental protection, legal enforcement, and ecological recovery. Limitation: This research is limited to analyzing one court decision, so it is not yet able to provide a comprehensive picture of the implementation of the trilogy of legal objectives in similar cases in Indonesia. Contribution: This research contributes to understanding the implementation of the trilogy of legal objectives in the criminalization of environmental crime cases. The findings can serve as a reference for policy makers and legal practitioners to design a more balanced approach to punishment.